Age, Sex and Strain Respond Differently to Acute Ritalin (Methylphenidate) Exposure - Kabani, Asif A.; Yang, Pamela B.; Dafny, Nachum (International Journal of Innovative Research in Medical Science, 2021)
The dose-dependent response to variable methylphenidate (MPD) doses on the behavior of male and female adolescent (post-natal day 39) and adult (post-natal day 60) rats of three different genetic strains was studied to examine whether there are sex, age and strain dependent differences in response to MPD. Twenty-four male and twenty-four female groups were used. The 48 groups each had an N=8. The results show that female adolescents and adult rats of Sprague-Dawley (SD) and Spontaneous Hyperactive Rat (SHR) strains were more sensitive to the acute exposure of MPD. Furthermore, female adult rats of the SD, SHR and Wistar-Kyoto (WKY) strains generally responded with greater increase in locomotor activity than the adolescent females of these strains. In the WKY strain, adolescent males tended to experience a greater increase in activity than adult males. Lastly, significant differences in response to MPD also were observed among the three genetic strains. These variable responses to the acute dose of MPD reinforce the need to study the effects of this psychostimulant across the various sexes, ages and strains.